The quality of locally-manufactured cornmill grinding plates (Journal of Science and Technology, 2016)
Maize was milled either ‘wet’ or ‘‘dry’’ using locally-manufactured milling plates. Samples of milled maize were taken and analyzed for elemental iron (Fe). Results show that iron particles from milling plates contaminates the milled maize and that the level of contamination increases with the quantity of milled maize. This is the case in both ‘wet’ and ‘dry’ milling. However, the relationship between the mass of elemental iron (Fe) in milled maize and mass of milled maize in ‘wet’ milling differed from that of ‘dry’ milling. That is, in ‘dry’ milling the rate of metal loss decreases at first and then increases with mass of milled maize, whereas in ‘wet’ milling, the rate increases monotonically with mass of milled maize. The difference could be explained in terms of the mechanism(s) or mode(s) of metal loss under the different milling conditions. In ‘dry’ milling, loss of metal is initially controlled by friction wear and later by erosion-corrosion. In the case of ‘wet’ milling metal loss could be attributed to conjoint action of corrosion and friction wear. The implications of these results are briefly discussed in terms of the possible health effects on consumers of foods prepared from such contaminated milled maize.